2019
DOI: 10.1111/liv.14135
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospitalizations for chronic liver disease‐related liver failure in the United States, 2005‐2014

Abstract: Background & Aims Current estimates of the population‐based disease burden of liver failure or end‐stage liver disease (ESLD) are lacking. We investigated recent trends in hospitalizations and in‐hospital mortality among patients with ESLD in the United States (US). Methods A retrospective analysis was performed utilizing the National Inpatient Sample from 2005 to 2014. We defined ESLD as either decompensated cirrhosis or hepatocellular carcinoma (HCC), criteria obtained from the International Classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
(49 reference statements)
2
49
0
Order By: Relevance
“…Genetic mutations in interaction with epigenetics and environmental factors, which may be present for Asians/Pacific Islanders, could also theoretically increase mortality in this patient group. Cirrhosis, especially with decompensation, has been known to increase in-hospital mortality for Asians/Pacific Islanders, which may also further explain our results [ 6 ].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Genetic mutations in interaction with epigenetics and environmental factors, which may be present for Asians/Pacific Islanders, could also theoretically increase mortality in this patient group. Cirrhosis, especially with decompensation, has been known to increase in-hospital mortality for Asians/Pacific Islanders, which may also further explain our results [ 6 ].…”
Section: Discussionmentioning
confidence: 58%
“…However, this is not the same for patients with cirrhosis-related complications, as can be seen in our study as well. Patients with cirrhosis-related complications continue to experience higher mortality rates, increased hospital LOS, and greater total hospital charges for all complications [ 5 , 6 ]. Our study further shows that high-risk cirrhosis patient populations, such as our cohort with pulmonary hypertension, also continue to have significantly higher mortality that is further magnified in association with deadly cirrhosis-related complications [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,9,18 A growing trend in the incidence of this fatal disease throughout the past decade has been observed in the USA. 2,18 In this study, although a different diagnostic criterion for ACLF was used, we also demonstrated a rise in the prevalence of ACLF in Southeastern China. Additionally, a correlation between the prevalence of ACLF and low temperature as well as high humidity was demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%